How Patriarchal Culture Localizes Human Trafficking Eradication Norm: Case Study on the Implementation of Human Trafficking Eradication Law in Indonesia - Gema Ramadhan Bastari (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
One of the main critical notes on the effort to combat trafficking in persons is the lack of victim protection in favor of criminal prosecution. This paper argues that this problem can be explained by looking at the norm that shapes the effort to eradicate human trafficking. In this paper, the author will employ norm localization theory to explain how the existing patriarchal culture in Indonesia is threatened by the norm of human trafficking eradication socialized by the Palermo Protocol and localizes the norm to sustain their existence. This will be done by studying the implementation of human trafficking eradication law in Indonesia, i.e. Law No. 21 of 2007 concerning the Eradication of the Crime of Human Trafficking. Ultimately, this paper finds that the norm of human trafficking eradication in Indonesia has been localized by reducing the definition of human trafficking to a crime of rape against women. This localized norm then complements the rape culture in Indonesia by allowing the continuation of victim blaming practice, which in turn denies the victim their right to receive protection and freedom of movement.